Unlocking Students’ Reading Power: Teacher Strategies and Pedagogical Challenges in EFL Classrooms - Munir Munir (Journal of Excellence in English Language Education, 2026)
This study examines instructional strategies employed by an English teacher to enhance students’ reading comprehension in an Indonesian junior high school context, alongside the challenges encountered during implementation. Guided by two research questions: (1) What strategies are used to improve students’ reading comprehension? and (2) What challenges are faced by the teacher? This study adopts a descriptive qualitative design. Data were collected through classroom observations, semi-structured interviews, and documentation. The findings reveal the implementation of three primary strategies: Question–Answer Relationship (QAR), scaffolding, and think-aloud protocols. These strategies facilitate comprehension by promoting text engagement, metacognitive awareness, and structured support. However, two major challenges persist: low student motivation and insufficient foundational English proficiency. The study highlights the critical role of adaptive pedagogy and strategic intervention in addressing these constraints. This research contributes to EFL pedagogy by demonstrating how strategy integration can improve reading comprehension while also emphasizing the importance of addressing affective and linguistic barriers in classroom practice.